ASSESSING THE LEVEL OF THE STUDENT'S READING COMPREHENSION ABILITIES AND THEIR DIFFICULTIES - Silaban, Veronika; Sembiring, Yenita Br; Lumbanbatu, Ira Maria Fran (Universitas Suryakancana, 2025)
Students can acquire and comprehend information from a variety of books because to reading comprehension, a crucial cognitive ability. Numerous internal and external elements, including vocabulary, prior knowledge, motivation, and interest in reading materials, might affect how difficult it is for students to comprehend what they read. The purpose of this study is to determine and examine the obstacles that students encounter when trying to understand texts, as well as the elements that lead to these obstacles. According to the study's findings, children frequently have trouble understanding at the inferential and evaluative levels, where they must draw connections between information that isn't presented in the text. Reading comprehension was also found to be significantly hampered by a lack of background information and a restricted vocabulary.